Agronomic performance of soybean cultivars under two sowing times in the savanna of Piauí State, Brazil - Alcântara Neto, Francisco de; Petter, Fabiano André; Pavan, Bruno Ettore; Schmitt, Cirio Régis; Almeida, Fernandes Antônio de; Pacheco, Leandro Pereira; Piauilino, Adelfran Cavalcante (Comunicata Scientiae, 2012)
The objective of this study was to evaluate the agronomic performance of soybean cultivars in anagricultural area located in the Serra do Quilombo (Cerrado of Piaui State, Brazil), in two growingseasons (2008/2009 and 2009/2010) and two sowing dates (15/12 and 03/01) were conducted fieldtrials of varieties, with randomized block design with four replications in a factorial 4 x 2. The cultivarswere M9144RR, M9056RR, M8867RR and P99R01. We evaluated the height of first pod, plant heightand grain yield. There was no significant effect on the parameters evaluated for sowing dates.The joint analysis between growing seasons and showed similar behavior in times of cultivars. Theaverage yield was not affected for sowing times within each season. The 2009/2010 season hadgrain yields significantly lower than those of the 2008/2009 season, due to the occurrence of waterdeficit during the vegetative stage to the beginning of the beginning of flowering and grain filling in2009/2010. We conclude that it is possible to soybean planting until early January in the area of Piauisavanna approached, indicating little effect of the photoperiod for that region.